Hazard assessment of Maerua subcordata (Gilg) DeWolf. for selected endpoints using a battery of in vitro tests. (15th September 2019) - Gebrelibanos Hiben, Mebrahtom; Kamelia, Lenny; de Haan, Laura; Spenkelink, Bert; Wesseling, Sebastiaan; Vervoort, Jacques; Rietjens, Ivonne M.C.M.
Abstract: Ethnopharmacological relevance: Maerua subcordata (Gilg) DeWolf is a medicinal and wild food plant growing mainly in east Africa. Especially its root tuber is widely used in traditional medicine to treat several infectious and chronic diseases but also in some toxicity implications like use as abortifacient. Aim of the study: the present study applied in silico and in vitro tests to identify possible hazards of M. subcordata (fruit, leaf, root, seed) methanol extracts focussing on developmental toxicity. Materials and methods: Ames test, estrogen receptor alpha (ERα) assay, aryl hydrocarbon receptor (AhR) assay, embryonic stem cell test (EST), and zebrafish embryotoxicity test (ZET) were employed. Besides, a Derek Nexus toxicity prediction was performed on candidate structures obtained from metabolomics profiling of the extracts using liquid chromatography coupled to multistage mass spectroscopy (LC/MS n ) and a MAGMa software based structural annotation. Results: Glucosinolates, which degrade to isothiocyanates, and biogenic amines were among the candidate molecules identified in the extracts by LC/MS n - MAGMa software structural annotation. Isothiocyanates and some other candidate molecules suggested a positive mutagenicity alert in Derek toxicity predictions. All the extracts showed negative mutagenicity in the Ames test. However, the Derek predictions also identified endocrine and developmental toxicity as possible endpoints of concern. This was further assessed using in vitro tests. Results obtained reveal that leaf extract shows AhR and ERα agonist activities, inhibited differentiation of ES-D3 stem cells into contracting cardiomyocytes in the EST (p < 0.001) as well as inhibited hatching (p < 0.01) and showed acute toxicity (p < 0.01) in the ZET. Also, the fruit extract showed toxicity (p < 0.05) towards zebrafish embryos and both fruit and seed extracts showed AhR agonist activities while root extract was devoid of activity in all in vitro assays. Conclusion: The leaf extract tests positive in in vitro tests that may point towards a developmental toxicity hazard. The current evaluations did not raise concerns of genotoxicity or developmental toxicity for the fruit, seed and root extracts. This is important given the use of especially these parts of M. subcordata, in traditional medicine and/or as (famine) food. Graphical abstract: Image 1